Синтез акрилатів з метилпропіонату та пропіонової кислоти на В₂О₃-Р₂О₅-ZrO₂/SiO₂ каталізаторі, промотованому основними оксидами - Івасів, Володимир Васильович; Піх, Зорян Григорович; Лапичак, Назарій Ігорович (НТУ "ХПІ", 2018)
Досліджено процес газофазної конденсації метилпропіонату та пропіонової кислоти з формальдегідом із утворенням метакрилової кислоти та метилметакрилату в присутності каталізаторів на основі оксидів бору і фосфору, промотованих сумішшю оксиду цирконію та основного оксиду. Встановлено вплив температури на конверсію, селективність і вихід цільових продуктів. Встановлено, що додавання метанолу підвищує селективність утворення метилметакрилату та сумарний вихід акрилатів.

Thiswork is devoted to development of the efficient catalysts for the synthesis of methacrylic acid and methyl methacrylate from methyl propionate, propionic acid and formaldehyde, which is one of the important stages of the industrial production of acrylates. The catalysts was developed based on oxides of boron and phosphorus, that were promoted by mixture of zirconium oxide and basic oxide selected from oxidesof sodium, potassium, cesium and calcium. The effect of temperature on the conversion of reactants, selectivity and yield of methyl methacrylate and methacrylic acid in the presence of the developed catalysts was determined. It was found that reactants conversion increases with temperature increase, while total acrylates selectivity decreases and total acrylates yield has maximum value at 623–653 K. It was established that the catalyst promoted by sodium oxide has highest total acrylates selectivity, while the catalyst promoted by calcium oxide has highest total acrylates yield. Maximum methyl methacrylate selectivity was obtained on the catalyst promoted by cesium oxide, hence this catalyst was chosen as the best. Also the effect of adding methanol to reactants was determined on this catalyst. It was found that adding methanol increases methyl methacrylate selectivity and total acrylates yield. Optimum conditions were determined to be temperature 623 K and residence time 12 s at which total acrylates yield is 41.0 %.
Synthesis of acrylates from methyl propionate and propionic acid on В₂О₃-Р₂О₅-ZrO₂/SiO₂ catalyst promoted by basic oxides
Keywords: метакрилова кислота; метилметакрилат; альдольна конденсація; формальдегід; температура; methacrylic acid; methyl methacrylate; aldol condensation